Design of Palm Oil Transport Information Systems at CV. Simatahari - Putra Mustakim Nasution, Putra Mustakim Nasution; Hasdiana, Hasdiana; Nurjamiyah, Nurjamiyah (Al'Adzkiya, 2020)
Transportation is the movement of goods or people from one place to another using a tool or vehicle. Transportation system in the CV. Simatahari is still manual, if the farmer wants to transport palm oil, the farmer first contacts the company via telephone to inform the transportation schedule and address. This often results in mistakes from the company when recording the schedule and address for transporting oil palm. One solution is to create a web-based palm oil transportation information system. The research method used in the manufacture of transportation information systems namely design thinking methods, programming languages using PHP and MySQL are used as databases. The results of this study can facilitate farmers in ordering oil palm transportation in real-time and also can find out information on the price of oil palm per kilo and transportation wages. Keyword: Transportation System, Palm Oil, Website, Design Thinking